2015
DOI: 10.3390/en81012266
|View full text |Cite
|
Sign up to set email alerts
|

A First-Order Study of Reduced Energy Consumption via Increased Thermal Capacitance with Thermal Storage Management in a Micro-Building

Abstract: This study uses a first-order approximation of a micro-building to investigate the major factors determining how increased thermal capacitance (ITC) with thermal storage management (TSM) can reduce energy consumption in locations with relatively mild weather conditions such as the southeastern part of the United States of America. In this study, ITC is achieved through water circulation between a large storage tank and pipes embedded within the building envelope. Although ITC results in a larger dominant time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The requirements for these valves are listed in Table 5. A large water tank was used to significantly increase the time constant of the building [19]. To retain a large thermal time constant and reduce the size of the tank, a phase change material (PCM) was added.…”
Section: Itc/tsm Model With Pcmmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirements for these valves are listed in Table 5. A large water tank was used to significantly increase the time constant of the building [19]. To retain a large thermal time constant and reduce the size of the tank, a phase change material (PCM) was added.…”
Section: Itc/tsm Model With Pcmmentioning
confidence: 99%
“…If these methods used permanent installations, such as buildings constructed with a high thermal mass, then benefits could have been lost when a low thermal capacitance is favorable. Due to this, investigations into active thermal mass and thermal storage methods are of interest [14][15][16][17][18][19]. Carpenter et al [16] found building energy consumption reduced when implementing increased thermal capacitance though water circulation in the shell of the building.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been previously used in [14,20,55,59], among other works, to capture first-order transients without having to perform a heavily-detailed building simulation that would require an extensive previous knowledge of the buildings and their processes. Another advantage of having a relatively simple building model is that it also facilitates the real-time implementation in control systems, such as the optimization framework we propose in this work.…”
Section: Thermodynamic Modelsmentioning
confidence: 99%
“…While [26,55,58] acknowledge the importance of variable COP, limitations with the black-box simulation software they employed precluded them from modeling a variable COP. We adapted the work of [56,62], where COP for heating and cooling were modeled as a quadratic function for a fixed supply temperature based on regressions from catalog data.…”
Section: Contribution Of the Mechanical Heating/cooling Systemmentioning
confidence: 99%
See 1 more Smart Citation